PECULIARITIES OF THE USE OF SUCCINATE AS AN ENERGETIC SUBSTRATE OF TISSUE RESPIRATION WHEN VITAMIN E IS ACCUMULATED IN LIVER OF POULTRY - Костюк, І. О. (Scientific Progress & Innovations, 2014)
The study of the peculiarities of the use of succinate as an energetic substrate of the tissue respiration is actual in connection with the use of the above acid (succinate) in the ration of animals and in veterinary medicine as one of the factors of metabolic correction. The investigation of the effect of membranotropic substances, namely vitamin E, on the oxidation of succinate by liver metochondria is important for the effective use of metabolic correction. The stimulation of free oxidation of succinate in liver mitochondria under the influence of high doses of vitamin E in the ration of hens has been shown. It should be taken into consideration when both vitamin E and succinate are used as energotrope factors of metabolic correction in poultry.